DEVELOPING STRATEGIES AND EVALUATION OF HOTS-BASED LEARNING ON THEMATIC LEARNING IN ELEMENTARY SCHOOL - Seka Andrean (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
Education is an important component of a nation. Developed nations must have a good education system. The purpose of this research is to find out how to develop strategies and evaluation of hots-based learning in thematic learning in elementary schools. The method used is the approach of library research through library sources related to learning strategies and evaluations in thematic learning as well as various other literature sources. Then analyzed and presented the findings of the data objectively. The results showed that higher order thinking skills (HOTS) learning carried out by teachers in improving the quality of learning, teachers must design scenarios of the learning process. To support this, it is administratively stated in the Learning Implementation Plan (RPP). A teacher must prepare teaching materials, learning resources, learning media/props, and test instruments to measure students' learning outcomes. The spirit of a HOTS learning is in the core activities. At this stage teachers practice design, models, strategies, and learning methods. There are several learning models that are recommended to be implemented by teachers in the learning process, such as: project-based learning, problem-based learning, problem solving, and inquiry/discovery. In the assessment process must be adjusted to the competency achievement indicators that will be measured using relevant instruments and able to stimulate students' critical thinking ability.